Alfven wave instability based on temperature anisotropy with non-maxwellian distribution function - Qureshi, M.N.S.; Saeed, Sundas; Shah, H.A. (Вопросы атомной науки и техники, 2013)
Space observations by numerous satellites reveal that the distributions often possess non-Maxwellian characteristics such as high energy tails or flat top (broad shoulders) in the profile of distribution functions. Distributions with high energy tails are well modelled by family of kappa type distribution. However, when distributions contain flat tops with or without high energy particles, generalized (r,q) distribution function is the best choice. In general the spectral index r corresponds to the flat part of the distribution and q to the high energy tail in the profile of the distribution function. By following the kinetic theory, we employ this distribution function to study the Alfven waves in anisotropic plasma and found that Alfven wave can grow when there is temperature anisotropy in plasma. Instability conditions are then studied for different temperature ratios by using the plasma parameters observed downstream the bow shock by CLUSTER.